Genome sequence of the olive tree, Olea europaea. Issue 1 (December 2016) - Cruz, Fernando; Julca, Irene; Gómez-Garrido, Jèssica; Loska, Damian; Marcet-Houben, Marina; Cano, Emilio; Galán, Beatriz; Frias, Leonor; Ribeca, Paolo; Derdak, Sophia; Gut, Marta; Sánchez-Fernández, Manuel; et al.
Abstract Background The Mediterranean olive tree (Olea europaea subsp.europaea ) was one of the first trees to be domesticated and is currently of major agricultural importance in the Mediterranean region as the source of olive oil. The molecular bases underlying the phenotypic differences among domesticated cultivars, or between domesticated olive trees and their wild relatives, remain poorly understood. Both wild and cultivated olive trees have 46 chromosomes (2n). Findings A total of 543 Gb of raw DNA sequence from whole genome shotgun sequencing, and a fosmid library containing 155, 000 clones from a 1, 000+ year-old olive tree (cv. Farga) were generated by Illumina sequencing using different combinations of mate-pair and pair-end libraries. Assembly gave a final genome with a scaffold N50 of 443 kb, and a total length of 1.31 Gb, which represents 95 % of the estimated genome length (1.38 Gb). In addition, the associated fungusAureobasidium pullulans was partially sequenced. Genome annotation, assisted by RNA sequencing from leaf, root, and fruit tissues at various stages, resulted in 56, 349 unique protein coding genes, suggesting recent genomic expansion. Genome completeness, as estimated using the CEGMA pipeline, reached 98.79 %. Conclusions The assembled draft genome ofO. europaea will provide a valuable resource for the study of the evolution and domestication processes of this important tree, and allow determination of the genetic bases of key phenotypic traits. Moreover, it will enhance breeding programs and the formation of new varieties.